Odpowiedzi

Najlepsza Odpowiedź!
2010-03-15T17:40:36+01:00
A) 2(x+3)= 10
2x+6=10
2x=10-6
2x=4
x=2
b)3(x-1)+2=8
3x-3+2=8
3x=9
x=3
c)2(13-x)-9=1
26-2x-9=1
2x= -16
x= -8
d) 3(1-x)+2=-7
3-3x+2=-7
3x=-12
x=-4
e) 3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8+1-9
0=0
f) 4(3x+2)+5(2x+3)= -(2x+13)
12x+8+10x+15=-2x-13
24x= -36
x=24/-36
x=-2/3
g) 4(x-2)-2(x-4)=2(2x-1)+6(x+1)
4x-8-2x+8=4x-2+6x+6
-8x=8
-x=1
x=-1
1 5 1
2010-03-15T17:43:08+01:00
A) 2(x+3)=10
b) 3(x-1) +2=8
c) 2(13-x)-9=1
d) 3(1-x)+2=-7
e) 3(x+3)=2(x+4)+x+1
f) 4(3x+2) +5(2x+3)= -(2x+13)
g) 4(x-2) -2(x-4)=2(2x-1)+6(x+1)

a) 2x+6=10
2x=10-6
2x=4/:2
x=2
b) 3x-3+2=8
3x=8+3-2
3x=9/:3
x=3
c) 26-2x-9=1
-2x+17=1
-2x=1+(-17)
-2x=-16/:(-2)
x=8
d) 3-3x+2=-7
-3x+5=-7
-3x=-7-5
-3x=-12/:(-3)
x=4
e) 3x+9=2x+8+x+1
3x+9=3x+9
3x-3x=9-9
0=0
f) 12x+8+10x+15=-2x-13
22x+23=-2x-13
22x+2x=-13-23
24x=-36
g) 4x-8-2x+8=4x-2+6x+6
2x=10x+4
2x-10x=4
-8x=4/:(-8)
x=-0,5

Nie jestem pewna przykładu F, ale reszta jest na pewno dobrze ! ; ))